Correlation between posterior tooth loss and temporomandibular joint disorders in elders: A cross-sectional study - Tulak, Jemima Karynhapukh; Wibisono, Jane Amelia Vebriani; Sumantri, Dominica Dian Saraswati (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2024)
Introduction: Tooth loss is one of the essential factors of oral health status, which affects individual quality of life and social factors. It is also a common oral health problem in adults and elders. A prolonged period of tooth loss, followed by an immediate replacement with dentures, can cause changes in occlusion due to the teeth' unsustainability; tooth position shift followed by extrusion leads to occlusion pattern disruption, resulting in gingival movement difficulties. This research analyses the correlation between posterior tooth loss and temporomandibular joint disorders in elders. Methods: Analytic observational with cross-sectional study. The sampling technique was simple random sampling, identifying a population of 39 people aged 60 to 75, consisting of 12 males and 27 females. The sample size was determined by the overall population size, calculated through the minimum single sample size formula incorporating the correlation coefficient (r). The primary data was obtained by completing the questionnaires and the respondents' clinical examination with the Helkimo index. Results: The findings showed that most respondents were female, 27 compared to 12. In terms of dysfunctional index data for tooth loss, the